The urgency of digital technology in education: a systematic literature review - Putra, Johni Eka; Sobandi, A; Aisah, Aisah (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2024)
The research objective is to investigate the urgency, impact, efforts, and challenges in integrating digital technology in education in Indonesia, with a focus on improving the quality of learning, reducing gaps in educational access, and preparing students to face a future integrated with technology. This research uses the Systematic Literature Review (SLR) method with 171,000 articles from Scopus, ERIC and Google Scholar sources (2018-2024 period), using the keyword "digital technology in education". Inclusion and exclusion criteria were applied to select 10 high-quality articles relevant to the research topic. The data analysis stage involved narrative synthesis of the 10 articles, reflecting the urgency of digital technology in improving the quality and effectiveness of education. The result of this work is that the use of digital technology in education is important and urgent to prepare the young generation to face the challenges of a digitalized future. E-learning, integration of ICT and AI, and digitalization of education improve the quality of learning and student experience. Digital literacy, digital learning media, and the role of technology in the teaching and learning process are important focuses. The integration of digital technology creates inclusive, dynamic and adaptive learning. Novelty provides an in-depth understanding of the challenges and opportunities in implementing digital technology in education in Indonesia, with a focus on remote areas and limited infrastructure. The implications of digital technology are expanding access.